DISSECTING THE NATIONAL EDUCATION POLICY, 2020 FOR SCHOOL AND HIGHER EDUCATION - et. al., Jitendra Paliwal (International Journal of Modern Agriculture, 2021)
India’s education system had been in dire need of an overhaul for a long time, with its last policy on education being crafted in 1986 and modified in 1992. No wonder, with time, the 1985-policy had become archaic and irrelevant, and called for reforms that would make the Indian education system fall in sync with international best practices. To exemplify, the erstwhile policy laid tremendous emphasis on rote learning, and performed abysmally when it came to practical implementation of the theory. What’s more, there was little importance given to research, which resulted in Indian Universities performing rather alarmingly in international university rankings. The overall system was also extremely rigid, and failed to offer students the freedom to take up their desired field for studies as well as to opt out in the middle. All of the aforesaid, inter alia, constituted reasons as to why big-ticket educational reforms were needed. Finally, resting years of anticipation, the Union Cabinet gave its nod to the National Education Policy, 2020 on July 28, with which India now stands on the cusp of a major educational revolution. The new policy attempts to completely revamp a broken system by way of introducing novel and unprecedented measures. However, as is nature’s supreme law, perfection is a myth. Even as the new policy introduces major reforms that have been long awaited, there are various areas that the policy has either not covered or if it has- called for amends and further deliberation. This paper studies the National Education Policy in great detail and dissects the hits and misses thereof. In conclusion, some suggestions are also proposed to address the problems identified in the new policy. The author relied on secondary sources for research..